Signals from the government: policy disagreement and the transmission of fiscal shocks - Giovanni Callegari; Jacopo Cimadomo; Giovanni Ricco (European Central Bank (ECB), 2016)
We investigate the effects of fiscal policy communication on the propagation of government spending shocks. To this aim, we propose a new index measuring the coordination effects of policy communication on private agents' expectations. This index is based on the disagreement amongst US professional forecasters about future government spending. The underlying intuition is that a clear fiscal policy communication can coalesce expectations, reducing disagreement. Results indicate that, in times of low disagreement, the output response to fiscal spending innovations is positive and large, mainly due to private investment response. Conversely, periods of elevated disagreement are characterised by muted output response.
Keywords: E60; D80; 330; disagreement; fiscal transmission mechanism; government spending shock